Cholangiocarcinoma: A Comprehensive Review and Update Guideline - Nugraha, Kadek Nandita; Hardyningrat, Baiq Inna Dwi; Kirana, Devi Chandra; Yahya, Najla Aulia; Ishlahi, Salsabila Dinda Nuril; Kadarisma, Shofia; Djannah, Fathul (Postgraduate, University of Mataram, 2024)
Cholangiocarcinoma is a rare cancer of the gastrointestinal system. However, the prognosis for people with this disease has not improved in the last decade. CCA has a poor prognosis because most cases are diagnosed at an advanced stage and the availability of treatment options is limited. This literature review aims to provide information regarding the current understanding and guidelines for cholangiocarcinoma. In this literature review, we searched the National Center for Biotechnology Information (NCBI) and Google Scholar using the search keywords